DIAGNOSIS, PREVENTION AND TREATMENT OF THROMBOEMBOLIC COMPLICATIONS IN THE EARLY POSTOPERATIVE PERIOD. (Journal of Universal Science Research, 2024)
This article outlines the prevention and diagnosis, as well as treatment of thromboembolic complications.